Sleeping with the enemy: unravelling the symbiotic relationships between the scale worm Neopolynoe chondrocladiae (Annelida: Polynoidae) and its carnivorous sponge hosts. Issue 1 (30th December 2020) - Taboada, Sergi; Serra Silva, Ana; Díez-Vives, Cristina; Neal, Lenka; Cristobo, Javier; Ríos, Pilar; Hestetun, Jon Thomassen; Clark, Brett; Rossi, Maria Eleonora; Junoy, Juan; Navarro, Joan; Riesgo, Ana
Abstract: The North Atlantic deep-water polynoid worm Neopolynoe chondrocladiae is involved in an exceptional symbiotic relationship with two hosts: the carnivorous sponges Chondrocladia robertballardi and Chondrocladia virgata . While this is an obligate symbiotic relationship, its real nature is unclear. We used a multidisciplinary approach to narrow down the type of symbiotic relationship between symbiont and hosts. Molecular connectivity analyses using COI and 16S suggest that N. chondrocladiae has high potential for dispersal, connecting sites hundreds of kilometres apart, likely aided by oceanographic currents. Microbial analyses on different anatomical parts of five Chondrocladia species suggest that the presence of the worm in C. robertballardi does not affect the microbiome of the sponge. MicroCT analysis on N. chondrocladiae show that it has dorsally oriented parapodia, which might prevent the worm from getting trapped in the sponge. A faecal pellet recovered from the worm suggests that the polynoid feeds on the crustacean prey captured by the sponge, something corroborated by our stable isotope analysis. Light and confocal microscopy images suggest that N. chondrocladiae elytra produce bioluminescence. We propose that the worm might use bioluminescence as a lure for prey (increasing the food available for both the sponge and the polynoid) and thus fuelling a mutualistic relationship.